Propuesta de diseño del sistema de gestión seguridad y salud en el trabajo con base en el resolución 0312 para la empresa Tamricos de la ciudad de San José del Guaviare (2021)
This research is presented as a contribution to the improvement of the quality of life of workers through the design and implementation of the Occupational Health and Safety Management System, against the prevention of future risks of accidents and occupational diseases in the company TAMRICO Agua Natural Life, thus maintaining its sustainability. Among the main conclusions that were reached, there is undoubtedly an absence of the SG-SST in accordance with the provisions of current regulations, although the company since its operation has not presented accidents and occupational diseases, it has become important that it knows and adopts the improvement processes in order to anticipate the evaluation, recognition and control of risks that subsequently affect the safety and health of its workers.